Emergency preparedness of families of children with developmental disabilities: What public health and safety emergency planners need to know - Wolf-Fordham, JD, Susan; Curtin, MSW, Carol; Maslin, MEd, Melissa; Bandini, PhD, Linda; Hamad, PhD, Charles D. (American Journal of Recreation Therapy, 2014)
Objective: To assess the emergency preparedness knowledge, behaviors, and training needs of families of children with developmental disabilities (DD). Design: An online survey. Participants: A sample of 314 self-selecting US parents/guardians of children with DD, aged birth-21 years. Main outcome measures: 1) Preparedness self-assessment; 2) self-report regarding the extent to which families followed 11 specific preparedness action steps derived from publicly available preparedness guides; and 3) parent training and support needs. Results: Although most participants assessed themselves to be somewhat to moderately well prepared, even those who reported being “very well prepared” had taken fewer than half of 11 recommended action steps. Most participants expressed a need for preparedness support; virtually all the respondents felt that training was either important or very important. Conclusions: Children with disabilities are known to be particularly vulnerable to negative disaster impacts. Overall, parents in this study appeared under-prepared to meet family disaster needs, although they recognized its importance. The results suggest opportunities and methods for public health and safety planning, education and outreach to parents of children with DD who would benefit from targeted training such as information and skill building to develop effective family preparedness plans and connections to local emergency management and responders.